Option A Improved HIV-free Infant Survival and Mother to Child HIV Transmission at 9–18 Months in Zimbabwe - BUZDUGAN, Raluca (AIDS, 2016)
OBJECTIVE: We evaluated the impact of Option A on HIV-free infant survival and mother-to-child transmission (MTCT) in Zimbabwe. DESIGN: Serial cross-sectional community-based serosurveys. METHODS: We analyzed serosurvey data collected in 2012 and 2014 among mother-infant pairs from catchment areas (CAs) of 132 health facilities from 5 of 10 provinces in Zimbabwe. Eligible infants (alive or deceased) were born 9–18 months before each survey to mothers ≥16 years old. We randomly selected mother-infant pairs and conducted questionnaires, verbal autopsies and collected blood samples. We estimated: 1) the HIV-free infant survival and MTCT rate within each CA and compared the 2012 and 2014 estimates using a paired t-test, 2) number of HIV infections averted due to the intervention. RESULTS: We analyzed 7,249 mother-infant pairs with viable maternal specimens collected in 2012 and 8,551 in 2014. The mean difference in the CA-level MTCT between 2014 and 2012 was −5.2 percentage points (95% confidence interval (CI)=−8.1, −2.3, p<0.001). The mean difference in the CA-level HIV-free survival was 5.5 percentage points (95%CI=2.6,8.5, p<0.001). Between 2012 and 2014, 1,779 infant infections were averted compared to the pre-Option A regimen. The association between HIV-free infant survival and duration of Option A implementation was not significant at the multivariate level (p=0.093). CONCLUSIONS: We found a substantial and statistically significant increase in HIV-free survival and decrease in MTCT among infants aged 9–18 months following Option A rollout in Zimbabwe. This is the only impact evaluation of Option A and shows the effectiveness of Option A and Zimbabwe’s remarkable progress towards eMTCT.